Form Matters: Stable Helical Foldamers Preferentially Target Human Monocytes and Granulocytes. (19th January 2017) - Del Secco, Benedetta; Malachin, Giulia; Milli, Lorenzo; Zanna, Nicola; Papini, Emanuele; Cornia, Andrea; Tavano, Regina; Tomasini, Claudia
Abstract: Some hybrid foldamers of various length, all containing the (4 R, 5 S )‐4‐carboxy‐5‐methyloxazolidin‐2‐one (d ‐Oxd) moiety alternating with anl ‐amino acid (l ‐Val, l ‐Lys, orl ‐Ala), were prepared in order to study their preferred conformations and to evaluate their biological activity. Surprisingly, only the longer oligomers containingl ‐Ala fold into well‐established helices, whereas all the other oligomers give partially unfolded turn structures. Nevertheless, they all show good biocompatibility, with no detrimental effects up to 64 μm . After equipping some selected foldamers with the fluorescent tag rhodamine B, a quantitative analysis was performed by dose– and time–response fluorescence‐activated cell sorting (FACS) assays with human HeLa cells and primary blood lymphocytes, granulocytes, and monocytes. Among the cell types analyzed, the oligomers associated with monocytes and granulocytes with greatest efficacy, still visible after 24 h incubation. This effect is even more pronounced for foldamers that are able to form stable helices. Abstract : Where form is function : Hybrid peptide oligomers with helical frameworks can associate preferentially with inflammatory cells, regardless of their charge or chemical nature. Such foldamers can thus act as targeting agents for small‐molecule drugs, as they are intrinsically non‐cytotoxic at relatively high doses. Moreover, with sufficient length, they show a particular cell targeting preference; they are rapidly and more effectively internalized in human blood myeloid cells, such as monocytes and granulocytes.